An investigation into the psychological status and influencing factors among residents undergoing standardized training - Zhenhua Liu; Haoyuan Zhang; Haoyuan Zhang; Haoyuan Zhang; Yufei Zhang; Lifang Zhou; Yixuan Wu; Zihan Lang; Leyuan Zhang; Haoyu Zhang; Qianqian Yu (Frontiers in Medicine)
BackgroundPhysician mental health has become an increasingly urgent concern worldwide, yet little attention has been paid to the psychological wellbeing of resident physicians in China. This study aims to assess the mental health status of Chinese resident physicians and identify key demographic and professional factors associated with psychiatric symptoms.MethodsA cross-sectional survey was conducted among 276 resident physicians at Qilu Hospital, Shandong University. Participants completed a structured questionnaire that included demographic information and the Symptom Checklist-90 (SCL-90) to evaluate psychological distress. Residents were classified as screening positive for psychiatric symptoms if they met any of the following criteria: a total score ≥160, more than 43 items rated ≥1 (mild), or at least one item rated ≥3 (moderate). Statistical analyses included independent-sample t-tests, chi-squared tests, and binary logistic regression to identify influencing factors.ResultsAmong 276 respondents, 20.1% screened positive for psychiatric symptoms. Compared to the Chinese general population, residents showed significantly elevated scores in obsessive symptoms (p < 0.001), depression (p = 0.029), anxiety (p < 0.001), hostility (p < 0.001), phobic anxiety (p < 0.001), and paranoia (p = 0.007). Logistic regression analysis revealed that longer training years (OR = 2.24, p = 0.011) and having a partner (OR = 48.44, p < 0.001) were associated with higher odds of psychiatric symptoms. Conversely, urban residence (OR = 0.15, p < 0.001), being an only child (OR = 0.35, p = 0.020), and holding a physician’s license (OR = 0.15, p < 0.001) were protective factors. No significant associations were observed for gender, education level, training identity, or household monthly income.ConclusionChinese resident physicians experience a high burden of psychological distress, with multiple risk and protective factors identified. These findings highlight the need for tailored mental health interventions, including improving working conditions, strengthening professional support systems, and addressing interpersonal and career-related pressures during residency training.